Comparison of Hydrogen Elimination from Molecular Zinc and Magnesium Hydride Clusters. Issue 35 (25th July 2014) - Intemann, Julia; Sirsch, Peter; Harder, Sjoerd
Abstract In analogy to the previously reported tetranuclear magnesium hydride cluster with a bridged dianionic bis‐β‐diketiminate ligand, a related zinc hydride cluster has been prepared. The crystal structures of these magnesium and zinc hydride complexes are similar: the metal atoms are situated at the corners of a tetrahedron in which the vertices are bridged either by dianionic bis‐β‐diketiminate ligands or hydride ions. Both structures are retained in solution and show examples of H−⋅⋅⋅H− NMR coupling (Mg: 8.5 Hz; Zn: 16.0 Hz). The zinc hydride cluster [NN‐(ZnH)2]2 thermally decomposes at 90 °C and releases 1.8 equivalents of H2. In contrast to magnesium hydride clusters, there is no apparent relationship between cluster size and thermal decomposition temperature for the zinc hydrides. DFT calculations reproduced the structure of the zinc hydride cluster reasonably well and charge density analysis showed no bond paths between the hydride ions. This contrasts with calculations on the analogous magnesium hydride cluster in which a counter‐intuitive H−⋅⋅⋅H− bond path was observed. Forcing a reduced H−⋅⋅⋅H− distance in the zinc hydride cluster, however, gave rise to a H−⋅⋅⋅H− bond path. Such weak interactions could play a role in H2 desorption. The presumed molecular product after H2 release, a Zn(I) cluster, could not be characterized experimentally but DFT calculations predicted a cluster with two localized ZnZn bonds.